Perbandingan Pengelolaan Sampah Indonesia Dan Jepang - Tania, Sherina Astri; Dompak, Timbul (LPPM Universitas Putera Batam, 2024)
Comparison of waste management between Indonesia and Japan is an important topic in the context of global challenges to the environment. Indonesia, as a developing country with a large population, faces serious problems in managing waste, while Japan has been known as a country that is successful in this regard. This article presents a comparison between the two countries in terms of government policies, waste sorting and collection systems, waste processing infrastructure, recycling, community participation, and education. Even though Indonesia still faces various challenges, such as less than optimal policy implementation and limited infrastructure, there are positive efforts such as recycling and composting programs. On the other hand, Japan has succeeded in developing an efficient waste management system thanks to a combination of strict government policies, community participation, and advanced infrastructure and technology. In conclusion, commitment and cooperation from all parties is needed to achieve better and more sustainable waste management in Indonesia